2016
DOI: 10.3389/fneur.2016.00221
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death Syndrome – Role of Trigeminocardiac Reflex: A Review

Abstract: Sudden infant death syndrome (SIDS) is an unexplained death in infants, which usually occurs during sleep. The cause of SIDS remains unknown and multifactorial. In this regard, the diving reflex (DR), a peripheral subtype of trigeminocardiac reflex (TCR), is also hypothesized as one of the possible mechanisms for this condition. The TCR is a well-established neurogenic reflex that manifests as bradycardia, hypotension, apnea, and gastric hypermotility. The TCR shares many similarities with the DR, which is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 111 publications
(113 reference statements)
1
21
0
Order By: Relevance
“…Sometimes, it can be fatal. Our group demonstrated that the TCR phenomenon is not only limited to the clinical neurosurgical domain, it also has a possible influence on many conditions including bruxism, sudden death infant syndrome, obstructive sleep apnea, sudden death in adults, acute nonsurgical conditions (epistaxis) and forensic medicine [20,21]. Future investigations should reveal many more associations of TCR in various other neurological conditions.…”
Section: Tcr: Beyond Neurosurgerymentioning
confidence: 76%
See 2 more Smart Citations
“…Sometimes, it can be fatal. Our group demonstrated that the TCR phenomenon is not only limited to the clinical neurosurgical domain, it also has a possible influence on many conditions including bruxism, sudden death infant syndrome, obstructive sleep apnea, sudden death in adults, acute nonsurgical conditions (epistaxis) and forensic medicine [20,21]. Future investigations should reveal many more associations of TCR in various other neurological conditions.…”
Section: Tcr: Beyond Neurosurgerymentioning
confidence: 76%
“…We do not yet know the answer. But from examinations in sudden infant death [20], it seems that changes in the brainstem make the patients prone to the TCR and SCR.…”
Section: Importance Of the Tcr In Skull Base And Spine Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…[70] In addition, the role of the TCR in various sleep disorders was also highlighted recently. [71,72]…”
Section: Schaller Et Al In 1999 First Reported Tcr (Central Tcr)mentioning
confidence: 99%
“…Various manifestations of the TCR include the naso-cardiac reflex, peripheral TCR, the diving reflex (DR), and the central TCR ( 6 10 ). Interestingly, DR, a subtype of TCR, has been hypothesized to have a role in sudden infant death syndrome (SIDS) ( 11 ) and the TCR is also linked to sleep disorders like sleep-related bruxism (SB) ( 12 ). It is reported that sudden microarousals (MA) occurring in the brain due to airway obstruction during sleep cause tachycardia, which stimulates RMMA and teeth grinding that activate the TCR resulting in bradycardia.…”
Section: Introductionmentioning
confidence: 99%